2010
DOI: 10.1128/jb.00878-10
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Staphylococcus aureus Strain JKD6159, a Unique Australian Clone of ST93-IV Community Methicillin-Resistant Staphylococcus aureus

Abstract: Community methicillin-resistant Staphylococcus aureus (cMRSA) is an emerging issue that has resulted in multiple worldwide epidemics. We report the first complete genome sequence of an ST93-MRSA-IV clinical isolate that caused severe invasive infection and a familial outbreak of skin infection. This isolate is a representative of the most common Australian clone of cMRSA that is more distantly related to the previously sequenced genomes of S. aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…Rigid filtering yielded two nonsynonymous single- (Fig. 4A), which exhibits signatures of an inorganic phosphate (P i ) transporter that is designated pitA in S. aureus strain JKD6159 (41). PitA is predicted to contain seven transmembrane helices, with the A57V mutation being located in the second helix.…”
Section: Resultsmentioning
confidence: 99%
“…Rigid filtering yielded two nonsynonymous single- (Fig. 4A), which exhibits signatures of an inorganic phosphate (P i ) transporter that is designated pitA in S. aureus strain JKD6159 (41). PitA is predicted to contain seven transmembrane helices, with the A57V mutation being located in the second helix.…”
Section: Resultsmentioning
confidence: 99%
“…The sequencing of the whole genome of multiple S. aureus strains, 123 followed by those of methicillin-resistant 124,125 and vancomycin-intermediate 126 and epidemic 127 strains undoubtedly marked a significant step forward. The subsequent development of bioinformatics to manipulate and analyze these data has facilitated high-throughput genomic, transcriptomic and proteomic analyses of microbial growth and pathogenesis.…”
Section: Vaccinesmentioning
confidence: 99%
“…Based on its genome sequence, ST93, like USA300, contains α-hemolysin, PVL and PSM-α (Chua et al, 2010) gain, no overt novel virulence determinant has been identified in ST93 that could easily explain its high virulence capacity, suggesting the contribution of altered gene expression or subtle genetic alterations in the core genome. Furthermore, it is tempting to speculate that, while ST93 is highly virulent, the lack of an obvious fitness factor, such as the ACME- arcA - speG system in USA300, might account for its relatively limited geographic distribution.…”
Section: Community-associated Mrsamentioning
confidence: 99%